A Review on Grid Integration Challenges of Wind Energy Systems - Dr. Ajit P. Chaudhari; Ashwini J. Patil; Gaurav B. Patil (International Journal of Engineering and Management Research, 2022)
In recent decades, the strengthening of electric energy security and the reduction of greenhouse gas emissions acquired great traction. The integration of large-scale intermittent renewable energy resources (RER) such as wind energy into existing electrical systems has risen dramatically in recent years. In the last few years, however, this integration creates several operational and control issues that impede the process. Grid functioning must be reliable and stable. This article will look at the problems that have been documented as a result of the recommended solutions techniques and the integration of wind energy Among the many difficulties, Generation uncertainty, power quality difficulties, angular and voltage stability, and reactive power support are all factors to consider. The ability to ride through faults is examined and explored. Aside from that, there are financial, environmental, and political factors to consider.